ENERGI TERBARUKAN DENGAN MENGGUNAKAN FLOATING SOLAR PHOTOVOLTAICS (FPV) - Nurdiansyah, Robby (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2025)
Floating Solar Photovoltaics (FPV) is the latest innovation in renewable energy that offers great potential to meet global energy needs while reducing environmental impact. In the search for more sustainable and environmentally friendly alternatives to generate electricity, FPV has emerged as an attractive solution. This technology combines two key elements of solar photovoltaic panels and water, by installing solar panels on the surface of water, such as lakes, reservoirs, or even the sea. Floating Solar Photovoltaics not only represents an advancement in photovoltaic technology, but also creates new opportunities to address energy and environmental challenges. In this way, this technology represents an important meeting point between renewable energy and wise management of water resources. In this guide, we will explore the basic principles, benefits, challenges, and potential applications of FPV in the context of an increasingly sustainable global energy economy. Through Floating Solar Photovoltaics, we can maximize the use of abundant sunlight to generate electricity, while preserving water quality and the precious aquatic environment. This approach has the potential to transform the global energy landscape in a sustainable way and reduce our carbon footprint. Let us delve deeper into the concept of FPV and explore how this technology can help us achieve our renewable energy and environmental goals.